The devil notebooks - Rickels, Laurence A. (University of Minnesota Press, 2008)
Milton's Paradise Lost. Goethe's Faust. Aaron Spelling's Satan's School for Girls? Laurence A. Rickels scours the canon and pop culture in this all-encompassing study on the Devil. Continuing the work he began in his influential book The Vampire Lectures, Rickels returns with his trademark wit and encyclopedic knowledge to go mano a mano with the Prince of Darkness himself. Revealing our astonishing obsession with Satan in his many forms, Rickels guides us on an entertaining and enlightening journey down the darkest corridors that film, music, folklore, theater, and literature have ever offere.